In praise of the common : a conversation on philosophy and politics - Casarino, Cesare (University of Minnesota Press, 2008)
A leading Marxist political philosopher and intellectual firebrand, Antonio Negri has inspired anti-empire movements around the world through his writings and personal example. Born in 1933, he was imprisoned in Italy in 1979 and convicted, nearly five years later, on questionable charges of "association and insurrection against the state," whereupon he left the country to teach in France. In 1997, he voluntarily returned to Italy to serve out his seventeen-year prison sentence. He was freed in 2003. In Praise of the Common, which began as a conversation between Negri and literary critic Cesar